Exploration of community perspectives towards Georgenholtz mission station as a heritage resource - Nemaheni, Tshimangadzo Israel (School of Architecture, Planning and Geomatics, 2021)
The turn of this century has been characterised by a flurry of research activities taking place around the history of Mission stations and missionaries in South Africa (SA). In Venda, in the Limpopo Province of SA, research about the Berlin Missionary Society (BMS) also gained momentum. Most of the researchers working in the area relied mainly on diaries, letters, annual reports, and limited published materials written by the BMS missionaries who worked at various mission stations in the area. These researchers focused on historical, educational, and religious developments, as captured by the Berlin missionaries. Of these historical accounts, the voices of the local communities have been hushed. Most of the stories available in written sources are from the viewpoints of the missionaries. At the same time, the focus of researchers in the heritage conservation fields has been on the physical condition of heritage properties, where the intention was to arrest deterioration of material. While there is a change in thinking in the heritage field to take into consideration the involvement of relevant stakeholders, the focus is still on the challenges related to the physical condition of heritage properties. Researchers in the heritage field have come to realise that conservation cannot unify or advance with any real innovation or vision if there is a continuation to concentrate the bulk of conservation discourse on issues of physical condition. This study addresses the issue of community participation in research by responding to the following question: What is the impact of community attitudes and perspectives towards Georgenholtz Mission Station (GHMS) as a heritage resource? Various community groupings were given the responsibility of airing their views regarding the Mission station as a heritage resource. In doing so, they were able to identify and articulate the values they associate with the mission station. Without an understanding of these values, practitioners, managers, and communities would be unable to act in respect of the gradual but rapid deterioration of the same heritage resource. Because of these values, communities were able to recommend what actions would be to the benefit of all of them. The research question of this study is answered through one-on-one oral interviews the researcher conducted with respondents. These respondents are divided into four categories of communities namely the youth, Lutheran Church leadership, Ha-Luvhimbi community leaders and members of families with historic ties with the Berlin Missionary Society. Individual respondents from these community categories were asked to comment upon the history of the Berlin Missionary Society and the development of Georgenholtz Mission Station from 1877 to the present times. They were also asked to broadly identify and explain the heritage significance of Georgenholtz Mission Station. The last question they were asked relates to what communities would like to see happening with Georgenholtz moving forward. The responses that came from these respondents show that Georgenholtz Mission Station has extensive connections to Mission history in rural South Africa which assists in conveying the significance of this Mission station beyond its importance to Ha-Luvhimbi village. Communities could identify various values attached to the Mission station, including amongst others, historical, aesthetic and architectural, social and economic values that should be preserved for the benefit of current and future generations. The results from this study indicate that communities interviewed regard Georgenholtz Mission Station as their heritage resource that should be taken care of and that there are economic benefits that could be derived from the adaptive reuse of the Mission station. The study concludes by outlining recommendations for further and extended research on the subject by other researchers.